2015
DOI: 10.1038/jcbfm.2015.171
|View full text |Cite
|
Sign up to set email alerts
|

Non-Additive Effects of Delayed Connexin Hemichannel Blockade and Hypothermia after Cerebral Ischemia in Near-Term Fetal Sheep

Abstract: Hypothermia is partially neuroprotective after neonatal hypoxic-ischemic encephalopathy. Blockade of connexin hemichannels can improve recovery of brain activity and cell survival after ischemia in near-term fetal sheep. In this study, we investigated whether combining delayed hypothermia with connexin hemichannel blockade with intracerebroventricular infusion of a mimetic peptide can further improve outcomes after cerebral ischemia. Fetal sheep (0.85 gestation) received 30 minutes of cerebral ischemia followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…For example, in fetal sheep after cerebral ischaemia, connexin hemichannel blockade reduced neuronal damage and restored EEG power (Davidson et al . 2012), but was non‐additive to mild hypothermia (Davidson et al . 2015 b ).…”
Section: The Mechanisms Of Hypothermic Neuroprotectionmentioning
confidence: 99%
“…For example, in fetal sheep after cerebral ischaemia, connexin hemichannel blockade reduced neuronal damage and restored EEG power (Davidson et al . 2012), but was non‐additive to mild hypothermia (Davidson et al . 2015 b ).…”
Section: The Mechanisms Of Hypothermic Neuroprotectionmentioning
confidence: 99%
“…Previous research has revealed that unopposed connexons also play an important role. They mediate the release of paracrine molecules, which in turn transmit cell death messages by the secretion of intracellular mediators (such as ATP, Nicotinamide adenine dinucleotide (NAD + ), and glutamate), which ultimately leads to cell edema [103,104]. …”
Section: Clinical Strategies Of Antioxidants In Hiementioning
confidence: 99%
“…Given that mild hypothermia is now standard of care, it is essential to test potential treatments in combination with hypothermia. This is particularly important as overlap with the wide array of reported mechanisms of action of hypothermia ( 47 ) may attenuate any additive effects, as discussed below ( 48 50 ). There are of course very large numbers of potential strategies; in this review we examine some leading examples, as summarized in Table 1 .…”
Section: Can Combination Treatment Augment Hypothermic Neuroprotectiomentioning
confidence: 99%